The TeO2-Na2O System: Thermal Behavior, Structural Properties, and Phase Equilibria - Kavaklioglu, Kutlu B.; Aydin, Suheyla; Celikbilek, Miray; Ersundu, A. Ercin (WILEY PERIODICALS, INC, 2015)
Thermal behavior, structural properties, and phase equilibria of the (100-x)TeO2-xNa(2)O system were studied in the 5 <= x <= 50 mol% composition range. Investigation of glass formation behavior in the binary system was realized, and the glass formation range was determined as 7.5 <= x <= 40 mol%. Differential thermal analysis (DTA) and Fourier transform infrared (FTIR) spectroscopy techniques were used for thermal and structural characterization of the glasses. Influence of Na2O content on glass transition temperature (T-g), glass stability (Delta T), density (rho), molar volume (V-M), oxygen molar volume (V-O), and oxygen packing density (OPD) values of sodium tellurite glasses was evaluated considering the structural transformations in the glass network. For the phase equilibria studies, DTA, X-ray diffraction (XRD), and scanning electron microscopy/energy dispersive X-ray (SEM/EDS) techniques were utilized to characterize the heat-treated samples. According to the phase equilibria studies, three eutectic regions were detected in the 0 < x < 50 mol% composition range of the (100-x)TeO2-xNa(2)O system. A new invariant endothermic reaction was detected for the compositions between 40 <= x <= 45 mol%. Na2O center dot 8TeO(2) (11.11 mol% Na2O) compound that was claimed to exist in the binary system in the literature was found to be the metastable delta-TeO2 phase.
Keywords: SODIUM TELLURITE GLASSES; TEO2 GLASSES; CRYSTALLIZATION; NA; CS; RB; LI; POLYMORPHS; TRANSITION; BINARY; Materials Science